Victim Recovery in Restorative Justice: A Theoretical Framework - Suzuki, Masahiro (Criminal justice and behavior, 2023)
Restorative justice was initially used for minor crimes, but it has been increasingly used to address the aftermath of violent crimes. Previous studies have indicated that restorative justice can be effective in reducing the harmful effects of violent victimization. However, there is limited research on how restorative justice can support victim recovery. This article presents a theoretical framework to better understand the relationship between victim recovery and restorative justice. The framework identifies core recovery factors that are common to victims of different types of violence, as well as those that are relevant to the restorative justice process. In addition, the framework highlights enabling factors that can facilitate the victim recovery process when present in restorative justice as well as inhibiting factors that can impede the victim recovery process if they are present in restorative justice.